Investigating How 'Social Media Influencers' Shape the Purchasing Decisions of Indian Customers in the Realm of Sustainable Organic Cosmetic Products (Journal of Informatics Education and Research, 2024)
‘Influence’ means the strength to finesse another person to do something that she/he might not want to do earlier. That could be a positive or negative action on anybody or anything. This mental ability of the influencer results in a new form of marketing strategy named ‘Influencer Marketing’. Business organizations have been using this influencer marketing strategy in their selling strategies starting with the development of social networking platforms. Though it appears to have gained traction recently, this is actually the older, simpler kind of word-of-mouth marketing that has been around for a while. Another possibility is that the influencer marketing strategy is a more developed form of the reference marketing plan. In this study, the researcher looked at how Indian consumers' purchasing decisions about organic cosmetics products are influenced by social media influencers. The aim of the research is, “To investigate the role and influence of 'social media influencers' on the purchasing behaviour of Indian customers in the realm of organic cosmetic products”. The purpose is to identify the impact of ‘social media influencers’ on buying behaviour of domestic customer towards organic products. Three different factors that are determined from the survey have been used to evaluate the purchasing behaviour. In order to get participant opinions, the study employs an exploratory research methodology and a survey method using a structured questionnaire. The convenience sampling approach, which is non-probability, is used to choose the participants. 200 replies were gathered from various regions in Uttar Pradesh. For the purpose of evaluating hypotheses, Liner Regression Analysis, Anova is used to assess the data is this research. Result of analysis shows, buying behaviours of the consumer is direct depends on the social media influencer.